Faktor yang Mempengaruhi Partisipasi Kerja Gen-Z di Indonesia - Wijaya, Nila Aristia; Arisetyawan, Kukuh (Universitas Negeri Surabaya, 2023)
Gen-Z is a generation that is currently in the productive age category and will enter the job market. However, the current problem is that the availability of job opportunities in Indonesia is smaller compared to the existing workforce. This research aims to determine the factors that influence Gen-Z work participation in terms of demographics and non-demographics. The method used in this research uses descriptive and inferential analysis, namely multinomial logistics. The research results show that all independent variables have a significant effect on the dependent variable where Gen-Z who are highly educated, have received training, are male and live in urban areas will tend to work in the formal sector, informal sector jobs. tend to be in rural areas and are dominated by men, while female unemployment still dominates. The percentage of Gen-Z absorbed into the job market is still very low, so more fundamental attention is needed regarding the young workforce.